PENGEMBANGAN BAHAN AJAR BERBASIS ANDROID DALAM PENGUASAAN MUFRODAT SISWA KELAS XII DI SMA COKROAMINOTO TAMALANREA MAKASSAR - Adhar, Adhar; Arsyad, Azhar; Yusuf T, Muh (Inspiratif Pendidikan, 2021)
This research examines the development of Android-based teaching materials. The aims of this research are, (1) analyzing the parts needed to produce ideal things for developing Android-based teaching materials, (2) developing Android-based Arabic language teaching materials in Arabic language learning, through a description of the operational parts of material production. Android-based Arabic language teaching, (3) validating Android-based Arabic language teaching material products that have been developed. The use of this research, for teachers, is of course that teaching assisted by the Android-based Canva application also helps in delivering and presenting practical and effective material. The research used in this case is a type of development (Research and Development) through a research and development (R&D) approach. R&D is research used to develop and validate educational products. This research focuses on the Hanafin and Peck development model with 4 main stages, namely: needs analysis, design, development and implementation. At the stage of implementing the design of the developing teaching materials, field testing was carried out, in this case the students of Cokroaminoto Tamalanrea Makassar High School were the test objects. Students were taken and selected as samples according to criteria by researchers including representatives of class XII. The validation technique refers to the Technology Acceptance Model (TAM). The research results show that Android-based Arabic language teaching material products have been tested and assessed through validation by experts in related fields. The validation percentage obtained from material experts obtained a validity percentage of 96.25% with very good assessment criteria. The percentage achieved by IT experts in the media and design aspects obtained a validity percentage of 92.18% with very good assessment criteria. The results of validation on students in small groups using the "r product moment" technique (i.e. the significance of r calculated on the r table) obtained a significance of r calculated > 0.468 (r tabl) for each indicator statement in the questionnaire and was declared valid.